Ultra-processed food consumption about body mass index (BMI) of public university students in Malaysia - Girijah Ganesrau,; Asma’ Ali,; Hamid Jan Jan Mohamed,; Ahmad Ali Zainuddin,; Hayati Mohd Yusof,; Sim, Why Jean (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Malaysian Nutrition Research Priorities for the 12th Plan (2021-2025) has identified a critical need for research on the consumption of ultra-processed foods among public university students in Malaysia. Despite this need, there is a lack of empirical research on the relationship between ultra-processed food intake and body mass index (BMI) in this population. To address this gap, this study aimed to investigate the relationship between the consumption of ultra-processed foods and BMI in public university students in Malaysia. A cross-sectional study design was employed, involving 250 respondents aged 18 years and above. Data was collected through a self-administered questionnaire, which consisted of three parts: a socio-demographic profile, anthropometric measurement, and a 24-hr dietary record. Food and beverage consumption was classified using the NOVA food categorization system (composed of Group 1: Unprocessed or minimally processed foods, Group 2: Processed culinary ingredients, Group 3: Processed foods, and Group 4: Ultra-processed foods), and energy intake was calculated using the Nutritionist Pro software and food guidance books. Statistical analysis was performed using SPSS version 20.0. The results showed that the average daily caloric intake was 1821.74 ± 439.03 kcal, with 31% of the total intake being contributed by ultra-processed foods (Group 4). The average energy intake from Group 1 and 2 was 1225.95 ± 414.90 kcal, Group 3 was 33.52 ± 73.83 kcal and Group 4 was 562.27 ± 344.71 kcal. The average BMI was 23.10 (7.38) kg/m2, which falls within the normal category. The analysis revealed a significant positive correlation between ultra-processed food consumption and BMI (rs=0.16, n=250, p=0.014). This study provides valuable insights into ultra-processed food consumption patterns among Malaysian university students using the NOVA classification system and highlights the importance of reducing such consumption to prevent nutritionally related diseases among public university students in the country.